2014
DOI: 10.1111/efp.12150
|View full text |Cite
|
Sign up to set email alerts
|

Fine root dynamics of oak saplings in response to Phytophthora cinnamomi infection under different temperatures and durations

Abstract: Summary The belowground effects of Phytophthora cinnamomi on 1‐year‐old saplings of two common oak species in mid‐Atlantic US forests, white (Quercus alba) and red oak (Q. rubra), were examined after incubation in pathogen‐infested soilless potting mix. Fine root lengths (0–1.5 mm in diameter) of both oak species were quantified after incubation at successive 30‐day intervals up to 300 days, for a total of 10 incubation periods. In addition, colony‐forming units (CFU) of P. cinnamomi were quantified after whit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 41 publications
(90 reference statements)
0
8
1
Order By: Relevance
“…Most significantly, both in the field and in pathogenicity tests P. cinnamomi -associated fine root losses were shown to be related to the propagule density of the pathogen. It was demonstrated that fine root losses are driving oak decline events in moist low-elevation stands where inoculum levels of the pathogen are higher and in areas like plant hardiness zones 6 and 7 where fine root regeneration is limited due to climatic constraints ( McConnell & Balci 2014a , b ).…”
Section: Soilborne Phytophthora Diseases In Forests and Woodlandsmentioning
confidence: 99%
“…Most significantly, both in the field and in pathogenicity tests P. cinnamomi -associated fine root losses were shown to be related to the propagule density of the pathogen. It was demonstrated that fine root losses are driving oak decline events in moist low-elevation stands where inoculum levels of the pathogen are higher and in areas like plant hardiness zones 6 and 7 where fine root regeneration is limited due to climatic constraints ( McConnell & Balci 2014a , b ).…”
Section: Soilborne Phytophthora Diseases In Forests and Woodlandsmentioning
confidence: 99%
“…Blockage of the xylem through hyphal obstruction and deposition of material by the plant inhibits water movement from the roots to the shoots, resulting in water stress (Ruiz G omez et al, 2015). Necrosis of infected fine feeder roots exacerbates the problem and can lead to rapid plant death (McConnell and Balci, 2015;Oßwald et al, 2014).…”
Section: Hyphal Growthmentioning
confidence: 99%
“…Sub-alpine regions were long considered free of P. cinnamomi because harsh environmental conditions were thought to limit its survival (Green 2016). Phytophthora cinnamomi becomes inactive in soil when the soil temperature drops below 10°C (Weste and Marks 1987), and no growth is shown on artificial media below 5°C (McConnell and Balci 2015). Podger et al (1990) modeled damage caused by P. cinnamomi in Tasmania and hypothesized that it is unlikely to cause disease in areas where annual mean temperature is less than 7.5°C.…”
Section: Introductionmentioning
confidence: 99%